Cgnl1, an endothelial junction complex protein, regulates GTPase mediated angiogenesis. Issue 14 (31st August 2017) - Chrifi, Ihsan; Hermkens, Dorien; Brandt, Maarten M; van Dijk, Christian G M; Bürgisser, Petra E; Haasdijk, Remco; Pei, Jiayi; van de Kamp, Esther H M; Zhu, Changbin; Blonden, Lau; Kros, Johan M; Duncker, Dirk J; et al.
Abstract: Aims: The formation of cell–cell and cell–extra cellular matrix (ECM) contacts by endothelial cells (ECs) is crucial for the stability and integrity of a vascular network. We previously identified cingulin-like 1 (Cgnl1) in a transcriptomic screen for new angiogenic modulators. Here we aim to study the function of the cell–cell junction associated protein Cgnl1 during vessel formation. Methods and results: Unlike family member cingulin, Cgnl1 expression is enriched in ECs during vascular growth. Cgnl1 is important for the formation of multicellular tubule structures, as shown in vitro using loss-of function assays in a 3D matrix co-culture system that uses primary human ECs and supporting mural cells. Further studies revealed that Cgnl1 regulates vascular growth by promoting Ve-cadherin association with the actin cytoskeleton, thereby stabilizing adherens junctions. Cgnl1 also regulates focal adhesion assembly in response to ECM contact, promoting vinculin and paxillin recruitment and focal adhesion kinase signalling. In vivo, we demonstrate in a postnatal retinal vascular development model in mice that Cgnl1 function is crucial for sustaining neovascular growth and stability. Conclusions: Our data demonstrate a functional relevance for Cgnl1 as a defining factor in new vessel formation both in vitro and in vivo .